Optimization of measurement conditions of Kerr constant in optical active liquids on the example of castor oil. - Nowakowski, Krystian; Perek, Artur; Izdebski, Marek; Ledzion, Rafał; Górski, Piotr (Wydawnictwo Politechniki Łódzkiej, 2014)
The results of measurements of Kerr constant in castor oil, obtained by dynamic-polarimetric method are presented. Variable optical path length and four measurement setup configurations were used. They differed by the orientation of polarizer and of quarterwave plate and therefore they were non-equivalent when other, unwanted effects occurred. It was shown that the Kerr constant measurement performed with use of only one system configuration and one length of optical path may be strongly affected by other effects, however taking the arithmetic mean of two results obtained from appropriate system configurations significantly reduces this error. Theoretical dependences were fitted to the experimental results, which allowed for approximation of other constants, like dichroism, linear birefringence and optical activity induced by external electric field (electrogyration).

Przedstawiono wyniki pomiarów stałej Kerra w oleju rycynowym metodą polaryzacyjno-optyczną dla różnych długości drogi światła w próbce przy czterech konfiguracjach pomiarowych, nierównoważnych pod względem wpływu innych niepożądanych efektów, które różnią się orientacjami polaryzatora i płytki ćwierćfalowej. Pokazano, że pomiar stałej Kerra przeprowadzony dla tylko jednej konfiguracji pomiarowej przy jednej długości drogi światła w próbce może być obciążony znacznym wkładem kilku innych niepożądanych efektów, jednakże obliczenie średniej arytmetycznej z pomiarów w dwóch odpowiednio dobranych konfiguracjach pomiarowych pozwala na znaczne zredukowanie błędów pomiarowych. Do wyników doświadczalnych dopasowano zależności teoretyczne, co oprócz pomiaru stałej Kerra pozwoliło także na zgrubne oszacowanie innych wielkości takich jak dichroizm, liniowa dwójłomność i aktywność optyczna indukowana polem elektrycznym (elektrożyracja).
Optymalizacja warunków pomiaru stałej Kerra w cieczach aktywnych optycznie na przykładzie oleju rycynowego
Keywords: olej rycynowy; technika polaryzacyjno-optyczna; kwadratowy efekt elektrooptyczny; aktywność optyczna; dichroizm; castor oil; optical polarimetric technique; quadratic electrooptic effect; optical activity; dichroism